Backend Developer in 30 Days Acquire Skills on API Designing, Data Management, Application Testing, Deployment, Security and Performance Optimization (English Edition) - Marquez-Soto, Pedro; Marquez-Soto, Pedro (BPB Publications, 2022)
Build stronger support system to power your enterprise applicationsKey Features? Figure out the most important elements of backend and application development.? Know how to construct large-scale, distributed applications using industry best practices and software architecture principles.? Provides a career map for becoming a successful backend developer, including advice on skills and tools.DescriptionIn today's world, becoming an experienced backend developer is a difficult job that requires a lot of work. There are an excessive number of stacks and technologies to master, and new ones often gain popularity. Nonetheless, they share the same fundamental concepts: data storage, security, performance, testing, etc.This book aims to teach and train you to become a successful backend developer with a solid skill set in developing and implementing the real engine of a successful enterprise application. Implementation topics like setting up a web server, designing and developing APIs, creating and running automated tests, and working with various types of databases are all addressed in detail. The book prepares developers to maintain the safety and security of their applications through the use of procedures that avoid application and data breaches. While you learn about every part of backend development, the book teaches you how to deal with errors and find and fix problems.By the end of the book, you will have a firm grasp on the fundamental principles that underpin backend programming, including application architectures, design patterns, essential development activities, and help for debugging.What you will learn? Gain knowledge to build the momentum of a solid backend developer and choose areas to investigate in depth.? Learn to integrate backend development as the top tech businesses do.? Comprehend the distinction between SQL and NoSQL, containers, APIs, and web servers.? Design large-scale systems step-by-step.? Grow from junior backend developer to senior developer, including the required skills and responsibilities.Who this book is forThis book would greatly benefit readers who are new to backend operations for web and mobile apps, such as junior software developers, web developers, application developers, and frontend and backend coders. Basic programming skills will help you practice this book's learnings. Table of Contents1. Building Multi-User Apps2. The Client-Server Architecture3. Designing APIs4. End-to-end Data Management5. Automating Application Testing6. Securing Applications7. Handling Errors8. Adopting Frameworks9. Deploying Applications10. Creating High-performance Apps11. Designing a System12. Bootstrap Your Career Path